The Integrative Effectiveness of Forensic Accounting and Control Tools in Enhancing Financial and Administrative Integrity: A Field Study - Saleh Yousif , Hasan (Iraqi Journal for Administrative Sciences, 2026)
This study aimed to analyze the impact of forensic accounting tools on enhancing financial integrity and administrative efficiency in government institutions in Nineveh. A sample of government employees was selected to represent the target population, and the study relied on an analytical and statistical approach using SPSS, along with an analysis of real corruption cases reported by the Integrity Commission. The results showed that applying forensic accounting tools has a significant positive effect on improving administrative and financial procedures and reducing violations, while other external factors also influence the outcomes. The study provided recommendations to strengthen the application of control tools, train staff, and establish regular monitoring mechanisms to ensure transparency and institutional efficiency.